2020
DOI: 10.30829/contagion.v2i2.7989
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Preferensi Jumlah Anak Ideal di Provinsi Sumatera Utara: Analisis Data Skunder SDKI 2017

Abstract: <p>Every family wants to have a certain number of children, this is inseparable from the value of children in each different family so sometimes a family wants 3 to 5 children. The ideal number of children owned by a person will frustrate the achievement of the 2 children program launched by the Indonesian government. The ideal number of children according to someone will be influenced by many things such as education, housing and access to information media. This study uses secondary data of 2017 IDHS u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The results of this study were in accordance with study conducted by Arsyad and Nurhayati's which stated that age at first marriage, exposure to information media, and preferences to have ideal number of children are related to the number of children owned by couples. 29 In addition, other studies also stated similar results with the above results. This study stated that age at first marriage, education and information exposure, preferences to have ideal number of children, and use of contraception have significant correlation with couples' ideal number of children.…”
Section: Discussionsupporting
confidence: 81%
“…The results of this study were in accordance with study conducted by Arsyad and Nurhayati's which stated that age at first marriage, exposure to information media, and preferences to have ideal number of children are related to the number of children owned by couples. 29 In addition, other studies also stated similar results with the above results. This study stated that age at first marriage, education and information exposure, preferences to have ideal number of children, and use of contraception have significant correlation with couples' ideal number of children.…”
Section: Discussionsupporting
confidence: 81%
“…The chi-square test results showed that maternal education was related to the mother's readiness to face menopause. In this case, it states that education is a tool that can receive knowledge and expand the mind so that it is easy to develop oneself to take action decisions (Sitorus, 2020). Mothers with low education find it difficult to accept innovation; most of them are less able to improve the welfare of their families.…”
Section: Resultsmentioning
confidence: 99%
“…Children have many meanings and functions for the family. Children are highly coveted both in the family of village people and city people (Sitorus et al, 2020). Babies can be born with normal weight because the mother fulfills balanced nutrition during pregnancy and the mother's regularity for routine pregnancy checks at the midwife.…”
Section: Discussionmentioning
confidence: 99%